Centre‐level variation of treatment and outcome in 5‐year‐old children with non‐syndromic unilateral cleft lip and palate: The Cleft Care UK study. Part 1: Methodology and results for dento‐facial outcomes. (June 2017) - Wills, A. K.; Mahmoud, O.; Hall, A.; Sell, D.; Smallridge, J.; Southby, L.; Toms, S.; Waylen, A.; Wren, Y.; Ness, A. R.; Sandy, J. R.
Structured Abstract: Objectives: Outline methods used to describe centre‐level variation in treatment and outcome in children in the Cleft Care UK (CCUK) study. Report centre‐level variation in dento‐facial outcomes. Setting and Sample Population: Two hundred and sixty‐eight five‐year‐old British children with non‐syndromic unilateral cleft lip and palate (UCLP). Materials and Methods: Between January 2011 and December 2012, data were collected on a comprehensive range of outcomes. Child facial appearance and symmetry were assessed using photographic pictures. Dental arch relationships were assessed from standardized dental study models. Hierarchical statistical models were used to predict overall means and the variance partition coefficient (VPC)—a measure of amount of variation in treatment or outcome explained by the centre. Results: Data on dento‐alveolar arch relationships and facial appearance were available on 197 and 252 children, respectively. The median age of the children was 5.5 years, and 68% were boys. Variation was described across 13 centres. There was no evidence of centre‐level variation in good or poor dento‐alveolar arch relationships with a VPC of 4% and 3%, respectively. Similarly, there was no evidence of centre‐level variation in good or poor facial appearance with a VPC of 2% and 5%, respectively. Conclusions: There was no evidence of centre‐level variation for dento‐facial outcomes although this study only had the power to detect large variation between sites.